A Feasibility Study on Professional Tourist Assistance Service (ProTAS) - Bangalan, Darwin P.; Martinez, Deanne; Parino, Maria Karren (Diliman, Quezon City College of Engineering, 2003)
The Department of Tourism, under the new secretary, Mr. Richard Gordon, launched WOW (Wealth of Wonders) Philippines campaign. However, it is only this year, 2003, that the actual advertising of the campaign had begun. Tourism-wise, the Philippines have a lot of potential when it comes to competing with neighboring Asian nations. This project study aims determine the feasibility of Professional Tourist Assistant Service (ProTAS) in several aspects like: market, organizational, technical, financial and social profitability. Also, it aims to increase the number of tourists in the Philippines through well performed service and through the design of a tourist assistance service that meets the need of these tourists and providing the proper information about the Philippines such as its history, culture, scenic spots, ships, restaurants etc. The Professional Tourist Assistance (ProTAS) is the first company that offers tourist assistance to tourists and gives flexible choices regarding accommodations and transportation. The target areas are the top 80% most visited places in the country. These are Cavite, Laguna, Baguio City, Cebu, Quezon, Davao City, Cagayan, Cagayan de Oro City, Butuan City, Aklan, Iloilo and Negros Occidental. From the survey conducted, tourists are very willing to avail of the service being offered with 76% of the population saying they would avail of the service being offered. While 88% says that they prefer packages, which is flexible over those that are fixed, meaning hotels and transportations are already preset. This translates to an increasing market share for the next five years. So, it was found that the project is indeed marketable. In establishing the organization for providing flexible service to Philippine tourists, the corporation was selected as the best type of ownership based on the following criteria: continuity of existence/business stability, lower investment risk, taxation, capital generation, and management flexibility. Also, stock corporation shall be formed. The Professional Tourist Assistance Service is determined to be a technically feasible project through the different techniques used in analyzing the data gathered from the secondary sources. The services offered include hotel accommodations, transportation services, and personal tourist assistance. Hotel accommodation service would be rendered by establishing partnership with several hotels accredited by the Department of Tourism located in each of the 13 places. Transportation services would be provided by the rent-a-car companies: Avis and Hertz Philippines. The facility layouts, that best suits the space requirements of each of the office area of the 12 regional offices are designed. These facilities will be located in Cavite in Lot 6 Block 3, Silang Crossing, Tagaytay City; in Sta. Rosa Laguna, along Loacan Road, Baguio City; Tabunok, Talisay City, Cebu; National Rd. Tagbakin, Atimonan, Quezon; Ma-a Road, Davao City; College Avenue, Tuguegarao City, Cagayan; Cagayan de Oro City l Libertad, Butuan City; Brgy. Yapak, Aklan; Concepcion, Iloilo; and In Brgy. Ugay, Bago City, Negros Occidental. However, because of the limited availability and capacity of financing institutions, it was found that for the five-year planning period, the only site that can be built is Cavite. The venture requires a total project cost of Php 30,285,003. Part of the project cost will be financed by the Philippine Tourism Authority (PHILTOA) through their Special Project Financing Services Division, which is an organization that funds projects that are supported by the Depart,emt of Tourism (DOT). The remaining balance will be shouldered by selling stocks to investors. The financial statements (income statement, cash flow statement and balance sheet), which were presented for the five-year study period, show a positive and increasing trend in the company?s net income and cash flow projections throughout the five-year operating period. Moreover, the financial ratios reveal a stable financial position for the company. Also, the computed net present value (NPV = Php 8,768,874) and internal ratio of return (IRR=127.94% > MARR) prove that the project is an acceptable venture. After the evaluation of the results of the financial projections and tests of profitability, the project is deemed to operate profitably, withstand adversities, and raise sufficient cash. Thus the project is considered financially feasible. The social profitability showed that the project has a significant impact in the community. This includes the generation of jobs, contributing to the municipal tax, corporate income tax, and personal income tax, which will help both the local government and the national government in funding. These taxes will be used to fund the projects for the country. Furthermore, qualitative benefits, like the motivation of other tourists to explore the wonders of the country were attributed to the project. This shows that ProTAS is indeed feasible.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Tour guides (Persons); Tourism; Participatory monitoring and evaluation (Project management)